INCREASED BIOLOGICAL PRODUCTIVITY THROUGH IRRIGATION DEVELOPMENT IN NIGERIA - ADEJUWON , J. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Reliable values of actual and potential biological productivity are computed using climatological data. Values of potential productivity vary from about 110 percent of actual productivity in the south to over 450 percent in the north. These indicate how much gain in productivity could be achieved through full irrigation in various parts of the country. However, locally available water is rather limited to make full irrigation possible in the far north. Thus the areas of greatest potential for irrigation agriculture are in the Middle Belt.